Unraveling the anticancer effect of curcumin and resveratrol - Pavan, Aline Renata [UNESP]; da Silva, Gabriel Dalio Bernardes [UNESP]; Jornada, Daniela Hartmann [UNESP]; Chiba, Diego Eidy [UNESP]; Dos Santos Fernandes, Guilherme Felipe [UNESP]; Chin, Chung Man [UNESP]; dos Santos, Jean Leandro [UNESP] (MDPI, 2016)
Resveratrol and curcumin are natural products with important therapeutic properties useful to treat several human diseases, including cancer. In the last years, the number of studies describing the effect of both polyphenols against cancer has increased; however, the mechanism of action in all of those cases is not completely comprehended. The unspecific effect and the ability to interfere in assays by both polyphenols make this challenge even more difficult. Herein, we analyzed the anticancer activity of resveratrol and curcumin reported in the literature in the last 11 years, in order to unravel the molecular mechanism of action of both compounds. Molecular targets and cellular pathways will be described. Furthermore, we also discussed the ability of these natural products act as chemopreventive and its use in association with other anticancer drugs.
Keywords: Anticancer; Cancer; Curcumin; Polyphenols; Resveratrol